2014
DOI: 10.1093/ndt/gfu255
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of multiple protein biomarkers to predict progression in diabetic chronic kidney disease

Abstract: The relationship of biomarkers with future progression of CKD is complex and depends in part on how CKD progression is defined. Biomarkers in the FGF-23 and VEGF-A pathways predicted patient progression independently of albuminuria levels in this patient cohort. Additional studies in other cohorts will help further validate this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 23 publications
3
50
1
1
Order By: Relevance
“…Not only is albuminuria a very strong (if not strongest) renal risk marker among all clinical characteristics, it also stands out against novel renal risk markers. A recent prospective observational study in patients with type 2 diabetes and CKD reported that multiple novel renal risk markers predicted the progression of renal disease (34). However, when Agarwal et al (34) adjusted their analyses for albuminuria, only fibroblast growth factor-23 remained statistically significantly associated with renal outcome.…”
Section: Albuminuria Predicts Renal Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Not only is albuminuria a very strong (if not strongest) renal risk marker among all clinical characteristics, it also stands out against novel renal risk markers. A recent prospective observational study in patients with type 2 diabetes and CKD reported that multiple novel renal risk markers predicted the progression of renal disease (34). However, when Agarwal et al (34) adjusted their analyses for albuminuria, only fibroblast growth factor-23 remained statistically significantly associated with renal outcome.…”
Section: Albuminuria Predicts Renal Outcomementioning
confidence: 99%
“…A recent prospective observational study in patients with type 2 diabetes and CKD reported that multiple novel renal risk markers predicted the progression of renal disease (34). However, when Agarwal et al (34) adjusted their analyses for albuminuria, only fibroblast growth factor-23 remained statistically significantly associated with renal outcome. This indicates that a large part of the renal risk predicted by these novel renal risk markers can be explained by their association with albuminuria.…”
Section: Albuminuria Predicts Renal Outcomementioning
confidence: 99%
“…A filtration marker (serum cystatin C), tubule-associated markers (neutrophil-gelatinase associated lipocalin, kidney injury molecule-1, liver fatty acid binding protein, N-acetyl-beta-D-glucosaminidase), and inflammatory markers (soluble tumor necrosis factor receptors) have been reported to improve prediction of DKD and progression to end-stage renal disease (ESRD) in type 2 diabetes (T2DM) [8, 9]. In the last 5 years, microRNA, a class of small non-coding RNAs, has emerged as additional potential diagnostic and prognostic biomarkers in renal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Also, intensive research has sought to identify biomarkers of diabetic kidney disease (DKD) progression. However, the performance of those markers for predicting DN or ESRD progression has been insufficient compared to the “gold standard” clinical measurements, estimated glomerular filtration rate (eGFR) and urine albumin-creatinine ratio (UACR) [11]. In particular, circulating blood or urinary microRNAs have been proposed to be novel tools for the diagnosis and prognosis of diabetes [8, 9].…”
Section: Introductionmentioning
confidence: 99%